(untitled) (World Economics and Finance Bulletin, 2021)
The article analyzes and illustrates the development of the Surkhandarya oasis fuel industry and the work of the Soviet government in this area on the basis of archival and statistical materials. The economy of the republic, in particular, the Surkhandarya oasis, the fuel industry is being formed on the basis of coal, oil and natural gas deposits found and mined underground. The oil industry, which plays an important role in the economy of our country, has a long history. The article covers the exploration, discovery and commissioning of primary oil fields in Uzbekistan